Effects of grasshoppers on prairies: Herbivore composition matters more than richness in three grassland ecosystems. (10th September 2018) - Laws, Angela N.; Prather, Chelse M.; Branson, David H.; Pennings, Steven C.
Abstract: Understanding how biodiversity affects ecosystem processes is a key question in ecology. Previous research has found that increasing plant diversity often enhances many ecosystem processes, but less is known about the role of consumer diversity to ecosystem processes, especially in terrestrial ecosystems. Furthermore, we do not know how general biodiversity responses are among ecosystem types. We examined the role of insect herbivore (Orthoptera) diversity on plant production using parallel field experiments in three grassland ecosystems (mixed grass prairie, tallgrass prairie and coastal tallgrass prairie) to determine whether the effects of grasshopper diversity were consistent among sites. Using mesocosms, we manipulated orthopteran species richness (0, 1, 2, 3 or 4 species), functional richness (number of functional feeding groups present; 0, 1 or 2 functional groups) and functional composition (composition of functional groups present; mixed‐feeders only, grass‐feeders only, both mixed‐feeders and grass‐feeders). Diversity treatments were maintained throughout the experiment by replacing dead individuals. Plant biomass was destructively sampled at the end of the experiment. We found no effect of species richness or functional richness on plant biomass. However, herbivore functional composition was important, and effects were qualitatively similar across sites: The presence of only grass‐feeding species reduced plant biomass more than either mixed‐feeding species alone or both groups together. Orthopterans had consistent effects across a range of abiotic conditions, as well as different plant community and orthopteran community compositions. Our results suggest that functional composition of insect herbivores affects plant communities in grasslands more than herbivore species richness or functional richness, and this pattern was robust among grassland types. Abstract : This paper examines how consumer diversity affects plant biomass among three sites using three parallel experiments. The authors find that the functional composition (feeding guilds) of the orthopteran community is more important than species richness across three very different sites.